Phenazine‐Based Ratiometric Hg2+ Probes with Well‐Resolved Dual Emissions: A New Sensing Mechanism by Vibration‐Induced Emission (VIE). Issue 47 (27th June 2016) - Zhou, Haitao; Mei, Ju; Chen, Yi‐An; Chen, Chi‐Lin; Chen, Wei; Zhang, Zhiyun; Su, Jianhua; Chou, Pi‐Tai; Tian, He
Abstract : Phenazines exhibit intriguing vibration‐induced emission (VIE) owing to the fast intrinsic vibration of benzo[a, c]phenazine moiety. For the first time, a phenazine‐based ratiometric fluorescent probe DBPST is developed for recognizing Hg 2+ via restriction of VIE. Upon binding with Hg 2+, DBPST demonstrates two well‐resolved emission peaks (over 130 nm) with a wide tuning color and affords a large signal‐to‐background ratio.